Happy Children: A Modern Emotional Commitment - Stearns, Peter N. (Frontiers in Psychology, 2019)
American parents greatly value children’s happiness, citing it well above other possible priorities. This commitment to happiness, shared with parents in other Western societies but not elsewhere, is an important feature of popular emotional culture. But the commitment is also the product of modern history, emerging clearly only in the 19th century. This article explains the contrast between more traditional and modern views, and explains the origins but also the evolution of the idea of a happy childhood. Early outcomes, for example, included the novel practice of hosting parties for children’s birthdays, another mid-19th-century innovation that has expanded over time. Explaining the intensification of the happiness commitment also reveals some of the downsides of this aspect of popular emotional culture, for example in measurably complicating reactions to childish unhappiness. The basic goal of the essay is to use this important facet of modern emotional history to evaluate a commitment that many modern parents assume is simply natural.